2021
DOI: 10.1186/s13765-021-00605-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fibers, micronutrients, and phytonutrients on gut microbiome: a review

Abstract: The human gastrointestinal tract harbors a magnitude of bacteria, which are collectively known as the gut microbiome. Research has demonstrated that the gut microbiome significantly impacts the health of its host and alters the host’s risk for various chronic diseases. Many factors, such as diet, could potentially be manipulated to alter the host gut microbiome and induce subsequent preventative and/or therapeutic effects. It has been established that diet partakes in the regulation and maintenance of the gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…The results of our study emphasize the importance of a high fiber diet for individuals who have genetic risk of vitamin D deficiency. The role of dietary fiber in relation to the vitamin D-GRS and BMI is not clear; however, both fiber and vitamin D are involved in the health and regulation of the gut microbiome [64]. Dietary fiber is known to have helpful effects on weight management due to their bulking effect and fermentation by the gut microbiota [65,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study emphasize the importance of a high fiber diet for individuals who have genetic risk of vitamin D deficiency. The role of dietary fiber in relation to the vitamin D-GRS and BMI is not clear; however, both fiber and vitamin D are involved in the health and regulation of the gut microbiome [64]. Dietary fiber is known to have helpful effects on weight management due to their bulking effect and fermentation by the gut microbiota [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…As for vitamin D, studies have demonstrated that vitamin D and its receptor, VDR, can regulate and influence gut microbiota [71,72]. Vitamin D has immune-modulatory properties such as inhibiting inflammation and infections and hence might be important in modifying gut microbiota [64]. As both fiber and vitamin D have anti-inflammatory properties, and both are potential modifiers of the gut microbiome, therefore, our gene-fiber intake interaction on BMI could be possibly a result of the influence of microbiome modulation brought about by reduced dietary fiber intake in participants with an increased genetic susceptibility to vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Poor diet and/or impaired bile acid processes-features of NAFLD-drive micronutrient malabsorption of essential vitamins and minerals. 57,172,173 Fat-soluble vitamins, in particular, require appropriate bile acid metabolism. Bile salts facilitate the absorption of dietary fats through the intestinal lining.…”
Section: Mnd and The Gut Microbiomementioning
confidence: 99%
“…Of note is that the interaction between gut microbiome and minerals is bidirectional meaning that while the microbiota can affect the absorption of minerals, its composition is also influenced by changes in the level of trace minerals. For instance, selenium status strongly correlates with a higher diversity of gut microbiome [ 68 ]. Therefore, it is not unreasonable to propose that LithoLexal ® Joint as a source of major and trace biominerals may provoke observable improvements in the dysbiotic microbiome of patients with osteoarthritis.…”
Section: Litholexal ® Joint a Natural Dmat For The Management Of Osteoarthritismentioning
confidence: 99%